Raziskovanje in preučevanje tehniške dediščine v funkciji narodove identitete - Papotnik, Amand; Brglez, Tina (Revija za elementarno izobraževanje, 2009)
Researching and studying technical heritage in the function of a nation's identity. With the topic of connecting technology with the research and study of technical heritage, it is necessary to emphasize that there is scientific and developmental work involved in determining the aspects, instruments and evaluation of the research results. The results can be compatible with scientifically technical, technically productive and/or technically creative work done on the elaboration of a sample (model, design, illustration, instrument, project) and with concrete material-technical heritage (e.g. mills, wells, presses, saws, hives, chests, etc.). The article also deals with the global aims of technology and the many aspects (technical, technological, physical, ergonomic, ecological, formative, organizational and economical) that need to be taken into consideration when making a sample evaluation of a material technical heritage. Certain measures should be taken in order to give assurance of preserving the technical heritage and its maintenance as a part of a fixed region, its suitable usage, as well as to put forward new developmental needs and strategies of the Republic of Slovenia and to preserve cultural diversity and cultural identity of the Slovene national territory.